Plasmin improves blood–gas barrier function in oedematous lungs by cleaving epithelial sodium channels. (11th May 2020) - Zhao, Runzhen; Ali, Gibran; Nie, Hong‐Guang; Chang, Yongchang; Bhattarai, Deepa; Su, Xuefeng; Zhao, Xiaoli; Matthay, Michael A.; Ji, Hong‐Long
Abstract : Background and Purpose: Lung oedema in association with suppressed fibrinolysis is a hallmark of lung injury. Here, we have tested whether plasmin cleaves epithelial sodium channels (ENaC) to resolve lung oedema fluid. Experimental Approach: Human lungs and airway acid‐instilled mice were used for analysing fluid resolution. In silico prediction, mutagenesis, Xenopus oocytes, immunoblotting, voltage clamp, mass spectrometry, and protein docking were combined for identifying plasmin cleavage sites. Key Results: Plasmin improved lung fluid resolution in both human lungs ex vivo and injured mice. Plasmin activated αβγENaC channels in oocytes in a time‐dependent manner. Deletion of four consensus proteolysis tracts (αΔ432‐444, γΔ131‐138, γΔ178‐193, and γΔ410‐422) eliminated plasmin‐induced activation significantly. Further, immunoblotting assays identified 7 cleavage sites (K126, R135, K136, R153, K168, R178, K179) for plasmin to trim both furin‐cleaved C‐terminal fragments and full‐length human γENaC proteins. In addition, 9 new sites (R122, R137, R138, K150, K170, R172, R180, K181, K189) in synthesized peptides were found to be cleaved by plasmin. These cleavage sites were located in the finger and the thumb, particularly the GRIP domain of human ENaC 3D model composed of two proteolytic centres for plasmin. Novel uncleaved sites beyond the GRIP domain in both α and γ subunits were identified to interrupt the plasmin cleavage‐induced conformational change in ENaC channel complexes. Additionally, plasmin could regulate ENaC activity via the G protein signal. Conclusion and Implications: Plasmin can cleave ENaC to improve blood‐gas exchange by resolving oedema fluid and could be a potent therapy for oedematous lungs.